New approaches for the study of faience using beads from Southern Portugal - Costa, Mafalda (2022)
A collection of 30 faience beads recovered from the Iron Age necropolis of Vinha das Caliças 4 (Beja, Portugal) was analyzed in order to identify their production technology and provide insights into their possible provenance. The multi-analytical approach employed, combining laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), variable pressure scanning electron microscope coupled with energy dispersive X-ray spectrometry (VP-SEM-EDS) and micro-X-ray diffraction (µ-XRD), highlights the difficulties that arise from the analysis of weathered faience objects, and which are augmented by their intrinsic heterogeneous nature. VP-SEM-EDS analysis and LA-ICP-MS mapping revealed that the disk-shaped faience beads were manufactured using the cementation glazing method. Copper, most likely in the form of bronze scrapings, was used to impart a blue-green hue to these beads. Micro-XRD also revealed that the disk-shaped beads were manufactured using feldspathic sand. On the other hand, the cubic-shaped bead, identified as an Egyptian blue frit by VP-SEM-EDS and μ-XRD, owes its vivid blue color to the tubular crystals of this well-known synthetic pigment. Trace element analysis suggests that all beads were manufactured in the Levant region using coastal sands. Ultimately, this study highlighted the importance of the use of a combination of microstructural and geochemical criteria in the identification of faience production technology and provenance. The importance of the selection of the sampling strategy in LA-ICP-MS analysis of weathered faience objects was also emphasized.